Digital humanities and visual project management: Use of tools in libraries - Viola, Helouíse Hellen de Godoi; Marli Dias de Souza Pinto (Advanced Notes in Information Science, 2023)
This paper stemmed from the understanding that technological tools for Visual Project Management have been configured as a part to be investigated within the scope of Digital Humanities. Therefore, it proposed identifying in the scientific literature whether these tools are used in libraries and what they are from a bibliographic survey carried out in the Web of Science database. This research is characterized as qualitative, exploratory, descriptive, and bibliographic. As for the results obtained, only one paper was identified that described the adaptation panels of the Notion tool for project management.